Fitting of Breakthrough Curve by Deactivation Kinetic Model for Adsorption of H2S from Syngas with Zn-Contaminated Soil - Ko, Tzuhsing (Asian Journal of Chemistry, 2015)
A deactivation kinetic model was used to predict the breakthrough curve for the adsorption of H2S from syngas with Zn-contaminated soil. The H2S adsorption experiments were carried out in a fixed-bed reactor at high temperature. Results indicated that the deactivation kinetic model can be well fitted the breakthrough curve within the experimental ranges. The breakthrough curves were accurately predicted and provided useful information for the time to reload the solid materials in the reaction. The activation energy of the reaction of Zn-contaminated soil and H2S was experimentally calculated about 126.4 and 42.2 kJ/mol, respectively for deactivation kinetic model I (m = 0, n = 1) and model II (m = 1, n = 1). Both of two types of deactivation kinetic models can fit the experimental results. The order of H2S dsorption in the deactivation model was probably ranged from zero to one.